Pregnancy complicated by HTLV‐1‐associated myelopathy/tropical spastic paraparesis (HAM/TSP): a case report - Hiroshi Mori; Eiji Shibata; Tomoichiro Kuwazuru; Takayuki Uchimura; Emi Kondo; Yukio Iwanaka; Kiyoshi Yoshino (Clinical Case Reports, 2021)
Abstract Pregnancy was not associated with deterioration of HAM nor was HAM associated with adverse pregnancy outcome in this case. These findings suggest that women with HAM/TSP, even those who use a wheelchair, should not be discouraged from pregnancy.